The Development of the Methodologies of Qur'anic Exegesis in Early Islam - Ushama, Thameem (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Development of the Methodologies of Qur'anic Exegesis in Early Islam